The effects of criminal propensity and strain on later offending - Craig, Jessica M. (Crime & delinquency, 2017)
Recently, Agnew has narrowed the focus of General Strain Theory by arguing certain factors must converge for criminal coping to occur. Specifically, individuals must have certain crime-related traits, experience strains that are perceived as unjust and high in magnitude, and occur in situations that encourage criminal coping. A longitudinal sample of serious adolescent offenders was used to assess the impact of direct and vicarious victimization on later offending among those with higher and lower criminal propensity. Regardless of their criminal propensity, youth who experienced victimization were more likely to engage in antisocial behavior compared with those who were not victimized. The results are mixed regarding Agnew’s thesis and suggest that victimization experiences may push justice-involved youth into further crime.